Continuing Classroom Action Research Toward Sustainable High School Teachers in Indonesia - Misdi Misdi; Nurani Hartini; Rina Destiana; Komarudin Komarudin (Perkumpulan Dosen Muslim Indonesia, 2022)
This paper reports a workshop series of community services conducted in a senior high school in Indonesia. This workshop series focused on the developing the school teachers’ comprehension about Classroom Action Research to promote their instructional professional development. For the data gathering, conferences were main technique in exploring and discovering their view points of the workshops. The results show that, regardless their barriers of being directly observed in classroom practices, the school teachers’ awareness of being professional teaching is improved. They become more motivated to attend the conference and enthusiastically involved in the discussion. Yet, barriers are also reported to show that limitation is also found during the workshop and services.